Metformin Effectiveness in Reducing Mortality among Covid-19 Patients with Type 2 Diabetes Mellitus at a Tertiary Hospital in Indonesia - Zihono, Yudivaniel; Yusmaini, Hany; Hasanah, Uswatun; Harfiani, Erna; Mokoagow, Md Ikhsan; Budiman, Dicky (Folia Medica Indonesiana, 2023)
Highlights: 1. As there is a scarcity of publications on the use of metformin for COVID-19 in Indonesia, the findings of this present study may contribute more insight to the existing body of research and provide data specific to the Southeast Asian population. 2. This study revealed a decreased mortality rate associated with metformin use in diabetic patients with mild to moderate COVID-19 infection. 3. This study suggests that diabetic patients may continue metformin treatment during a COVID-19 infection as the medication has sustained therapeutic effects. Abstract COVID-19 patients with comorbidities, such as type 2 diabetes (T2DM), have a higher mortality rate compared to those without any comorbidities. T2DM patients usually receive metformin as their first-line treatment. However, the effectiveness of metformin in reducing mortality rates still requires further analysis. The objective of this study was to analyze the effectiveness of metformin in reducing mortality rates among COVID-19 patients with T2DM. An analytic observational design with a retrospective cohort approach was used in this study. Samples were acquired from hospitalized COVID-19 patients with T2DM medical records at Fatmawati Central General Hospital, Jakarta, Indonesia, throughout 2020–2021. The samples were collected using a purposive sampling technique and analyzed using Chi-square test (p<0.05; RR<1). This study comprised 137 samples, with 56 samples receiving metformin and 81 not receiving metformin. The mortality rate in the sample group that received metformin was lower (19.6%) compared to the group that was not given the medication (38.3%). The Chi-square test results indicated a statistically significant relationship between metformin treatment and a lower mortality rate among COVID-19-contracted individuals with T2DM (p=0.020; RR=0.513). Therefore, this study concludes that the administration of metformin treatment reduces mortality among COVID-19 patients with T2DM.